2015
DOI: 10.2169/internalmedicine.54.2047
|View full text |Cite
|
Sign up to set email alerts
|

Refractory Status Epilepticus Caused by Anti-NMDA Receptor Encephalitis that Markedly Improved Following Combination Therapy with Rituximab and Cyclophosphamide

Abstract: We herein describe the case of a 48-year-old woman who presented with nonconvulsive status epilepticus refractory to antiepileptic drugs caused by anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis without any tumors. She developed nausea and psychiatric symptoms, followed by fever and an acute progressive disturbance of consciousness. On admission to our hospital, she presented with involuntary orofacial movements and central hypoventilation, and an electroencephalogram showed a generalized slow activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 12 publications
1
12
1
Order By: Relevance
“…Of all seizure types, generalized seizure was the most common seizure type, which was consistent with the reported seizure types of the disease . Furthermore, data about the incidence of RSE and SRSE are lacking; however, some case studies reported the occurrence of RSE and SRSE in the acute phase of anti‐NMDAR encephalitis . In our cohort, 14.8% RSE and 10.2% SRSE occurred in the acute phase of this disease.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Of all seizure types, generalized seizure was the most common seizure type, which was consistent with the reported seizure types of the disease . Furthermore, data about the incidence of RSE and SRSE are lacking; however, some case studies reported the occurrence of RSE and SRSE in the acute phase of anti‐NMDAR encephalitis . In our cohort, 14.8% RSE and 10.2% SRSE occurred in the acute phase of this disease.…”
Section: Discussionsupporting
confidence: 88%
“…Most patients develop generalized tonic–clonic seizures, whereas some exhibit a complex partial type . Status epilepticus (SE) was also reported . In addition, anti‐NMDAR encephalitis is one of the most common forms of autoimmune encephalitis that is associated with SE …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…If tumors are found, the surgical resection should be taken into account [1, 98]. When diagnosis is delayed, or patients do not have a tumor, or the first-line immunotherapy fails, additional treatment with second-line immunotherapy is usually applied [5, 11], which includes cyclophosphamide, rituximab, azathioprine, mycophenolate mofetil, methotrexate, and so on [99, 100]. Supporting therapies play an important role, for example antiepileptic and antipsychotic treatment, respiratory and cardiac support, management of blood pressure and temperature, and prevention of deep venous thrombosis (DVT) and bedsore [46, 101].…”
Section: Treatment Relapses and Outcomementioning
confidence: 99%
“…Status epilepticus can also be a manifestation of anti-NMDAR encephalitis. 16 Symptomatic treatment of movement disorders in anti-NMDAR encephalitis is challenging; antipsychotic medications, sedatives and sleep medications have been used to treat the symptoms with variable responses. It is recommended that anti-psychotic therapy be used for a short period to avoid extrapyramidal side-effects.…”
Section: Figure 1 Case 3: Initial Mr Images (Day 3 Of Admission): (A)mentioning
confidence: 99%